PENGARUH RELIGIUSITAS, LINGKUNGAN KERJA, DAN PENGETAHUAN AKUNTANSI SYARIAH TERHADAP MINAT BERKARIR DI SEKTOR PERBANKAN SYARIAH - Ramandha, Della Putri; Hasanah, Nuramalia; Armeliza, Diah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The purpose of this study was to determine and analyze how religiosity, work environment, and islamic accounting knowledge influence career interest in the islamic banking sector. The data sources used in this study are primary data, questionnaires were distributed to active students of the Accounting Study Program, State University of Jakarta using Google Form. Data analysis in this study used a multiple linear regression analysis model. The results of the study showed that religiosity and work environment have an influence on students' interest in a career in the islamic banking sector. While islamic accounting knowledge does not affect students' interest in a career in the islamic banking sector